THE ANALYSIS OF POSSIBILITIES OF INTERNET RESOURCES TO IMPROVE THE EFFICIENCY THE EDUCATIONAL PROCESS - Usmanov, S.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
In article the analysis of Internet resources of educational appointment is carried out and the short characteristic of the main opportunities of these resources is given. Today it is already impossible to present educational process without use of opportunities of Internet resources. The modern teacher has to be able to work with information which is necessary for realization of his professional activity, the solution of his professional tasks, to have skills of cooperation with pupils on the basis of information exchange. The educational Internet resource is complete, named, interconnected, uniform systemically organized set which includes both the general education formalized and professionally significant knowledge and means of organizational and methodical ensuring educational process and means for their automated storage, accumulation and processing. Internet resources are designed to satisfy needs of the user for various aspects and spheres of educational activity. Quite often concrete resource includes several properties such difficult at once on structure and functioning of means what the Internet is. Use of the Internet allows to establish between the teacher and pupils feedback when performing independent works, allows to carry out mailing of materials and to conduct surveys. Occupations with use of resources of the Internet represent alloy of new information technologies with new pedagogical technologies.